Effects of channel aspect ratio on microfluidic-chip design of hydrodynamic filtration for particle sorting - Chun, Byoungjin; Chun, Myung-Suk (IOP PUBLISHING LTD, 2019)
The model framework of hydrodynamic filtration was examined for the rational design of particle sorting, by considering the complete analysis of 3D laminar flow for flow fraction and complicated networks of main and multiple branch channels. As the objective parameters for tuning of the design, both the number of branch channels and each length of individual branches were decided for different aspect ratios (i.e. H/W = 0.5-2.5) of rectangular channel. In order to validate our model framework, we compared the results estimated by analytical model with those computed by numerical simulations. The number of branches and the their individual lengths decrease distinctly with increasing channel aspect ratio, so that a channel with deep geometry enables compact design of microfluidic-chip being operated by lower pressure drop under the same throughput condition. Pursuing the justification of this behavior, pressure drop, average fluid velocity, and the ratio of flow fraction at each branch point were quantified with variations of aspect ratios.
Keywords: INERTIAL MIGRATION; SEPARATION; FLOW; DEVICES; CELLS